Multimodal therapy for primary ureteral small cell neuroendocrine carcinoma with high-grade urothelial component: case report and literature review - Li, Yaqi; Deng, Yugang; Ma, Siwei; Liu, Jie (Frontiers in Urology, 2025)
Primary small cell neuroendocrine carcinoma (SCNEC) of the ureter is an exceptionally rare and aggressive malignancy, characterized by rapid progression and poor prognosis. Evidence regarding treatment with immune checkpoint inhibitors (ICIs) combined with neoadjuvant chemotherapy remains limited. We report the first documented case of ureteral SCNEC treated with a multimodal strategy incorporating programmed death-ligand 1 (PD-L1) inhibitors. A 57-year-old woman presented with a 15-day history of gross hematuria and 4 days of progressive left flank pain. Imaging revealed a left distal ureteral mass with hydronephrosis and suspected iliac lymphadenopathy. Stage IV high-grade urothelial carcinoma with small cell neuroendocrine differentiation of the ureter with regional lymph node metastases, confirmed by histopathology and immunohistochemistry (synaptophysin+, CD56+, Ki67 >75%). The patient received four cycles of neoadjuvant etoposide plus carboplatin chemotherapy, followed by radical left nephroureterectomy with bladder cuff excision. Adjuvant therapy included intravesical pirarubicin and six cycles of dual PD-1 blockade with toripalimab and vedicitumab. Post-neoadjuvant imaging showed a 60% reduction in tumor size. Pathology revealed R0 resection with marked tumor regression (Ki67 reduced to 40%). No recurrence was observed at 12-month follow-up. This case demonstrates the potential efficacy of integrating ICIs with standard treatment for advanced ureteral SCNEC. The durable response observed underscores the need for further research into early immunotherapy use and biomarker-guided therapeutic strategies.